Pertanggungjawaban Pidana Terhadap Pemalsuan Sertipikat Tanah Sporadis di Badan Pertanahan Nasional Bandar Lampung - Zainudin Hasan; S. Endang; Komang Widi Yane (Faculty of Law, Universitas Lampung, 2023)
Forgery of letters is crime that often occurs in people's lives. One of cases of crime forging letters is in court decision No: 139/Pid.B/2022/PN. Tjk. The problem in examination is whether the judge's legal considerations in imposing a crime on the defendant for crime of forging letters and how the criminal liability of the perpetrators of the crime of forging the letter. This is because it is necessary to know to what extent the imposition crime of forgery letters is at its level, whether it is subject to imprisonment and fines in accordance with mens area doctrine, as well as in looking at the crime committed and the circumstances justification or ballast. The approach used in this research is legal-normative approach and empirical law emphasizes the study of rule law, and the data used is secondary data and primary data. K Data collection was carried out through library research and field studies. In accordance with the results of the research and discussion, it appears that the basis for juridical considerations in the conviction perpetrators crime of forgery letters became the basis for revocation of name land deed, namely that actions defendant fulfilled elements first alternative indictment by prosecutor's office, in the end defendant was not proven and was found guilty of committing act of forgery of letters. If using letters can cause losses. As well as criminal liability for the perpetrators of the crime forging letters in accordance with Article 263 (2) Criminal Code and has fulfilled the theory of criminal liability. Suggestions for future are how to create criminal law that is accordance with the aspirations and values nation accordance with values justice for victims and perpetrators, namely upholding restorative justice effort to achieve peace without prioritizing concept retaliation which may not necessarily have deterrent effect.